Adoption of new flood forecasting technologies has improved Ecuador’s resilience and reduced the damage from extreme hydrological events. - Fernandes, Jose; Álvarez, Sophie (2023)
INAMHI- the National Institute and governing body of Meteorology and Hydrology of Ecuador – produces better flood forecasts with more accurate information on their timing, magnitude and impact. The Alliance, through SERVIR-Amazonia, contributed by training technicians from INAMHI and other Ecuadorian institutions to use the Tethys platform. This improved platform and training developed the organization´s flood forecasting practices, including the provision of more accurate information on the likely timing, magnitude and impact of floods, benefitting people across boundaries in the Amazon region.